Crystal of L-glufosinate ammonium and preparation method and application thereof
Patent Information
- Application Number
- CN202280096894.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-10
- Publication Date
- 2025-01-17
AI Technical Summary
The ammonium salt form of the existing L-glufosinate ammonium salt has insufficient crystallization thermal stability, which affects storage and transportation, and the zwitterionic form is acidic and corrosive in water, affecting agricultural equipment and the environment.
New crystal forms D and E of L-glufosinate ammonium salt are provided. They are prepared through specific X-ray powder diffraction patterns and thermal analysis characteristic peaks, using a cooling rate control method of organic solvents and water mixed solvents to form a crystal-free form. type, with excellent thermal stability and herbicidal effect.
The new crystalline forms D and E have significantly improved stability at high temperatures, have low hygroscopicity, and have a herbicidal effect of more than 85%. They are effective against acidic weeds and are non-corrosive, improving storage and transportation conditions.
Smart Images

Figure 00000018_0000 
Figure 00000018_0001 
Figure 00000019_0000
Abstract
Description
Crystallization of L-glufosinate ammonium salt and its preparation method and application Technical Field
[0001] The present invention specifically relates to the crystallization of L-glufosinate ammonium salt and a preparation method and application thereof. Background Art
[0002] L-glufosinate ammonium salt, chemically known as 4-[hydroxy(methyl)phosphonyl]-L-homoalanine, is the active ingredient in racemic glufosinate ammonium. Studies have shown that its herbicidal activity is twice that of the racemate. Its chemical structure is as follows:
[0003]
[0004] The crystal structure of the active ingredients of herbicides often causes differences in various physical and chemical properties of the drugs, such as solubility, dissolution rate, storage stability, hardness, etc. These differences directly affect the formulation process, storage method, separation method, pharmacokinetic performance, etc. of the herbicide, and thus affect the level, speed and difficulty of the herbicide's weed control.
[0005] At present, some research has been conducted on the crystalline form of L-glufosinate ammonium salt, such as Chinese invention patents CN111065270, CN109369713, CN110437276A, CN113831364A, CN113480573A, etc. The crystalline forms involved therein mainly include ammonium salt form, zwitterionic form or mixed crystals of the two. The zwitterionic form of L-glufosinate ammonium crystals will show strong acidity in water, and the formulated formulation is highly corrosive to agricultural equipment and the environment. Although the ammonium salt form of L-glufosinate ammonium crystals can avoid this problem to a certain extent, the currently available ammonium salt form of L-glufosinate still has insufficient thermal stability, which is not conducive to storage and transportation.
[0006] Summary of the Invention
[0007] The problem to be solved by the present invention is to provide a new crystal form D of L-glufosinate ammonium salt, which has both excellent thermal stability and herbicidal effect.
[0008] The present invention also provides a new crystal form E of L-glufosinate ammonium salt, which has both excellent thermal stability and herbicidal effect.
[0009] The present invention also provides methods for preparing the two crystals and applications of the two crystals in preparing herbicides.
[0010] In order to achieve the above object, a technical solution adopted by the present invention is:
[0011] A crystal of L-glufosinate ammonium salt, which is crystal form D of L-glufosinate ammonium salt and has characteristic peaks at 2θ angles of 8.583°±0.2°, 17.202°±0.2°, 18.398°±0.2°, and 23.001°±0.2°.
[0012] Furthermore, the X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 17.738°±0.2°, 21.977°±0.2°, 22.721°±0.2°, and 25.716°±0.2°.
[0013] Furthermore, the X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 32.980°±0.2°, 35.920°±0.2°, and 39.509°±0.2°.
[0014] According to some specific aspects of the present invention, the X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt has characteristic peaks at 2θ angles of 8.583°±0.2°, 17.202°±0.2°, 17.738°±0.2°, 18.398°±0.2°, 21.977°±0.2°, 22.721°±0.2°, 23.001°±0.2°, 25.716°±0.2°, 32.980°±0.2°, 35.920°±0.2°, and 39.509°±0.2°.
[0015] According to a specific aspect of the present invention, the X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt is shown in FIG1 .
[0016] According to some preferred aspects of the present invention, the crystalline form D of the L-glufosinate ammonium salt shows two endothermic peaks in the spectrum measured by differential scanning calorimetry, the starting temperatures of the two endothermic peaks are 139.5±2°C and 206.5±2°C, respectively, and the peak temperatures of the two endothermic peaks are 179.83±2°C and 218.80±2°C, respectively.
[0017] According to some preferred aspects of the present invention, the crystal form D of the L-glufosinate ammonium salt measured by thermogravimetric analysis shows that it loses 4.3±0.2% of its weight when heated from 139.5±2°C to 206.5±2°C.
[0018] According to a specific aspect of the present invention, the spectrum of the crystalline form D of the L-glufosinate ammonium salt measured by differential scanning calorimetry is shown in Figure 2, and the combined spectrum measured by differential scanning calorimetry and thermogravimetric analysis is shown in Figure 3.
[0019] According to the present invention, the crystalline form D of the L-glufosinate ammonium salt is an anhydrous crystalline form.
[0020] The present invention also provides a crystal of L-glufosinate ammonium salt, which is crystal form E of L-glufosinate ammonium salt. Its X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 8.884°±0.2°, 16.603°±0.2°, 17.459°±0.2°, 18.101°±0.2°, 18.658°±0.2°, and 23.224°±0.2°.
[0021] Furthermore, the X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 19.513°±0.2° and 33.221°±0.2°.
[0022] According to some specific aspects of the present invention, the X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt has characteristic peaks at 8.884°±0.2°, 16.603°±0.2°, 17.459°±0.2°, 18.101°±0.2°, 18.658°±0.2°, 19.513°±0.2°, 23.224°±0.2°, and 33.221°±0.2°.
[0023] According to a specific aspect of the present invention, the X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt is shown in FIG4 .
[0024] According to some preferred aspects of the present invention, the spectrum of the L-glufosinate ammonium salt crystalline form E measured by differential scanning calorimetry shows that the starting temperatures of the three endothermic peaks are 95.5±2°C, 147±2°C and 201±2°C, and the peak temperatures of the three endothermic peaks are 113±2°C, 185.8±2°C and 226.5±2°C, respectively.
[0025] According to some preferred aspects of the present invention, the crystalline form E of the L-glufosinate ammonium salt measured by thermogravimetric analysis shows that it loses 1.2±0.2% of its weight when heated from 95.5±2°C to 147±2°C, and loses 2.89±0.2% of its weight when heated from 147±2°C to 201±2°C.
[0026] According to a specific aspect of the present invention, the spectrum of the crystalline form E of the L-glufosinate ammonium salt measured by differential scanning calorimetry and the combined spectrum measured by thermogravimetric analysis are shown in FIG5 .
[0027] According to the present invention, the crystalline form E of the L-glufosinate ammonium salt is an anhydrous crystalline form.
[0028] Another technical solution provided by the present invention is a method for preparing the above-mentioned crystal form D of L-glufosinate ammonium salt, which comprises: adding L-glufosinate ammonium salt to an organic solvent, heating to 65-90°C for a first heat preservation, then cooling at a cooling rate with a difference between the external temperature (Tj) and the internal temperature (Tr) of Tj-Tr = 1 to 5K and cooling to -10 to 35°C, performing a second heat preservation, precipitating a solid, filtering the solid, and drying the obtained solid to obtain the crystal form D of L-glufosinate ammonium salt.
[0029] Another technical solution provided by the present invention is a method for preparing the crystalline form E of the above-mentioned L-glufosinate ammonium salt, which comprises: adding L-glufosinate ammonium salt to a mixed solvent of an organic solvent and water, heating to 65-90°C for a first heat preservation, then cooling at a cooling rate of 1-5K between the external temperature and the internal temperature to 40-60°C, performing a second heat preservation, then cooling at a cooling rate of 1-5K between the external temperature and the internal temperature to -10-35°C, performing a third heat preservation, precipitating a solid, filtering the solid, and drying the obtained solid to obtain the crystalline form E of L-glufosinate ammonium salt.
[0030] In some preferred embodiments of the present invention, in the process of preparing the crystalline forms D and E of L-glufosinate ammonium salt, the purity of the L-glufosinate ammonium salt is greater than or equal to 85%, and further greater than or equal to 92%.
[0031] According to the present invention, in the process of preparing the crystalline forms D and E of L-glufosinate ammonium salt, the L-glufosinate ammonium salt includes an amorphous form or other ammonium salt forms disclosed in the prior art.
[0032] According to some preferred aspects of the present invention, in the process of preparing the crystalline forms D and E of L-glufosinate ammonium salt, the organic solvent is a combination of one or more selected from alcohol solvents, ketone solvents and nitrile solvents.
[0033] Furthermore, the alcohol solvent is a combination of one or more of methanol, ethanol and isopropanol.
[0034] Furthermore, the ketone solvent includes acetone.
[0035] Furthermore, the nitrile solvent includes acetonitrile.
[0036] According to a specific aspect of the present invention, the organic solvent is methanol.
[0037] According to some preferred aspects of the present invention, in the process of preparing the crystalline forms D and E of L-glufosinate ammonium salt, the mass ratio of the L-glufosinate ammonium salt to the organic solvent is 1:1-20. Furthermore, the mass ratio of the L-glufosinate ammonium salt to the organic solvent is 1:1-10.
[0038] According to some preferred aspects of the present invention, in the process of preparing the crystalline form E of L-glufosinate ammonium salt, the feed mass ratio of the water to the organic solvent is 0.05-0.3:1.
[0039] According to some preferred aspects of the present invention, in the process of preparing the crystalline form D of L-glufosinate ammonium salt, the insulation temperature of the first insulation is 65-80°C, and the insulation time of the first insulation is 1-15h; further, the insulation time of the first insulation is 6-15h; according to a specific aspect of the present invention, the insulation temperature of the first insulation is 65-75°C, and the insulation time of the first insulation is 8-13h.
[0040] According to some preferred aspects of the present invention, in the process of preparing the crystalline form D of L-glufosinate ammonium salt, the insulation temperature of the second insulation is 15-35°C, and the insulation time of the second insulation is 1h-7 days; further, the insulation time of the second insulation is 10-36h; according to a specific aspect of the present invention, the insulation temperature of the second insulation is 25-35°C, and the insulation time of the second insulation is 20-30h.
[0041] According to some preferred aspects of the present invention, in the process of preparing the crystalline form E of L-glufosinate ammonium salt, the insulation temperature of the first insulation is 65-80°C, and the insulation time of the first insulation is 1-15h; further, the insulation time of the first insulation is 6-15h; according to a specific aspect of the present invention, the insulation temperature of the first insulation is 65-75°C, and the insulation time of the first insulation is 8-13h.
[0042] According to some preferred aspects of the present invention, in the process of preparing the crystalline form E of L-glufosinate ammonium salt, the holding temperature of the second insulation is 45-55°C, and the holding time of the second insulation is 0.1-3 hours. Further, the holding time of the second insulation is 0.5-2 hours. According to a specific aspect of the present invention, the holding temperature of the second insulation is 48-52°C, and the holding time of the second insulation is 0.8-1.5 hours.
[0043] According to some preferred aspects of the present invention, in the process of preparing the crystalline form E of L-glufosinate ammonium salt, the insulation temperature of the third insulation is 10-30°C, and the insulation time of the third insulation is 1h-7 days; further, the insulation time of the third insulation is 10-36h; according to a specific aspect of the present invention, the insulation temperature of the second insulation is 20-30°C, and the insulation time of the second insulation is 20-30h.
[0044] Another technical solution provided by the present invention is: a herbicide composition comprising an active ingredient and a carrier, wherein the active ingredient comprises at least one of the aforementioned crystalline form D and crystalline form E of the L-glufosinate ammonium salt.
[0045] The present invention also provides the use of the above-mentioned crystal in the preparation of herbicides.
[0046] To aid in understanding the various embodiments disclosed in this application, the following description is provided:
[0047] X-ray powder diffraction patterns are characteristic of specific crystal forms. When determining whether a crystal form is identical to a known crystal form, the relative positions of the peaks (i.e., 2θ) rather than their relative intensities should be considered. This is because the relative intensities of the spectrum can vary due to preferential orientation effects caused by differences in crystal conditions, particle size, and other measurement conditions. In particular, low-intensity peaks (intensity less than 20%) may not exist in some cases. The relative intensities of the diffraction peaks are not characteristic for determining the crystal form. In fact, the relative intensities of the diffraction peaks in the XRPD pattern are related to the preferred orientation of the crystal. The peak intensities shown here are illustrative and not for absolute comparison. In addition, it is known in the art that when measuring the crystallinity of a compound using X-ray diffraction, the 2θ values of the same crystal form can have a certain measurement error of approximately ±0.2° due to the influence of the measurement instrument or measurement conditions. Therefore, this error should be taken into account when determining each crystal structure. In XRD patterns, peak positions are typically expressed in 2θ angles or interplanar spacings (d). A simple conversion relationship exists between the two: d = λ / 2sinθ, where d represents the interplanar spacing (d), λ represents the wavelength of the incident X-ray, and θ is the diffraction angle. It should also be noted that in the identification of mixtures, some diffraction lines may be missing due to factors such as a decrease in content. Furthermore, experimental factors such as sample purity may cause an overall shift in peak angles, but a certain amount of shift is generally tolerated. Therefore, those skilled in the art will understand that the X-ray diffraction patterns of the crystal forms referred to herein do not necessarily have to be identical to those in the examples described herein. "Identical XRPD patterns" as used herein does not necessarily mean absolute identity; peak positions may differ by ±0.2° (or greater), and some variability in peak intensity is permitted. Any crystal form exhibiting a pattern identical or similar to the characteristic peaks in these patterns falls within the scope of this application. Those skilled in the art will be able to compare the patterns listed herein with those of an unknown crystal form to confirm whether the two patterns reflect the same or different crystal forms.
[0048] Based on a specific X-ray crystal diffraction pattern, those skilled in the art are generally permitted to select several characteristic peaks to define a crystal form. The selection of characteristic peaks is based on a comprehensive consideration of specific objectives and is not strictly limited. For example, those skilled in the art tend to select peaks with relatively high intensity, relatively low angles, and relatively complete peak shapes, as well as peaks that are sufficiently distinguishable from other crystals, so that the characteristic peaks have the significance of being distinguished, identified, and identified. Therefore, a change in the combination of selected characteristic peaks alone cannot be used to conclude that a different crystal form has been formed or that the crystal form range originally requested has been exceeded.
[0049] DSC measures transition temperatures when a crystal absorbs or releases heat due to structural changes or melting. For the same compound and the same crystalline form, the thermal transition temperatures and melting points typically remain within approximately 5°C in consecutive analyses. When a compound is said to have a given DSC peak or melting point, this refers to the DSC peak or melting point within ±5°C. It should be noted that for mixtures, the DSC peak or melting point may vary over a wider range. Furthermore, because melting is accompanied by decomposition, the melting temperature is related to the heating rate.
[0050] It should be noted that the numerical values and numerical ranges mentioned in this application should not be narrowly understood as the numerical values or numerical ranges themselves. Those skilled in the art should understand that they can fluctuate around specific numerical values based on different specific technical environments without departing from the spirit and principles of this application.
[0051] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0052] The present invention provides new crystal forms D and E of L-glufosinate ammonium salt. These two new crystal forms, based on low hygroscopicity, not only have excellent high-temperature stability (weight changes slowly only at about 140°C or even above 145°C, and remains essentially unchanged before that), but also have good weed control effects, achieving a plant control efficiency of over 85% against weeds such as sorrel, alopecurus, jatropha, and bluegrass. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] FIG1 is an XRPD spectrum of Form D of L-glufosinate ammonium salt prepared in Example 1;
[0054] FIG2 is a DSC spectrum of Form D of L-glufosinate ammonium salt prepared in Example 1;
[0055] FIG3 is a DSC-TGA combined spectrum of Form D of L-glufosinate ammonium salt prepared in Example 1;
[0056] FIG4 is an XRPD spectrum of Form E of L-glufosinate ammonium salt prepared in Example 2;
[0057] Figure 5 is a DSC-TGA combined spectrum of Form E of L-glufosinate ammonium salt prepared in Example 2. DETAILED DESCRIPTION
[0058] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are generally the conditions in routine experiments.
[0059] Unless otherwise specified in the following examples, all raw materials were purchased from commercial sources or prepared by conventional methods in the art.
[0060] In this application, the test instruments and conditions used in the experiment are as follows:
[0061] 1. The crystal form of the product was analyzed by X-ray powder diffractometer (XRD, Rigaku D / Max-2500, Cu Kα radiation, λKα = 0.15406 nm) with an emission voltage and current of 40 kV and 100 mA, respectively, a scanning range of 2-40°, a scanning step of 0.02°, and a scanning rate of 8° / min.
[0062] 2. Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA): DSC and TGA analyses were performed using a Mettler Toledo TGA / DSC 1 instrument. The DSC method was as follows: 5-10 mg of sample was placed in an aluminum crucible, which was then placed in the instrument. The nitrogen flow rate was set to 50 and 200 ml / min, and the temperature was increased from 30°C to 200°C at a rate of 10°C / min. Analysis was performed using Mettler Toledo's STAR software. The TGA method was as follows: 5-10 mg of sample was placed in a crucible, which was then placed in the instrument. The nitrogen flow rate was set to 20 and 50 ml / min, and the temperature was increased from 30°C to 200°C at a rate of 10°C / min. Analysis was performed using Mettler Toledo's STAR software.
[0063] In the following, Tj-Tr refers to the "difference between the external temperature and the internal temperature", where the external temperature is equivalent to the temperature of the cold source (the part that absorbs heat and cools down), and the internal temperature refers to the temperature of the mixed solution. The cooling rate Tj-Tr = 1K ~ 5K means that during the cooling process, the difference between the external temperature and the internal temperature always remains at 1-5°C, that is, the external temperature and the internal temperature both keep changing dynamically and always maintain a difference of 1-5°C.
[0064] Example 1: Preparation of Form D of L-glufosinate ammonium salt
[0065] L-glufosinate ammonium salt (100 g, 0.48 mol, amorphous) was added to methanol (300 g), heated to 68 ° C, kept warm for 10 hours, cooled to 25 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, solid precipitated, filtered, and dried to obtain L-glufosinate ammonium salt crystal form D.
[0066] The XRPD analysis of the resulting crystalline form shows a spectrum as shown in Figure 1. Characteristic peaks are observed at diffraction angles 2θ = 8.583° ± 0.2°, 17.202°, 18.398°, and 23.001°, with a 2θ error range of ±0.2°, confirming the existence of this new crystalline form. Its X-ray powder diffraction data are shown in Table 1.
[0067] Table 1: XRPD patterns
[0068]
[0069] The quantitative content of the product was 99.01% based on a standard sample without crystal water. Ion chromatography analysis showed that the ammonium content was 9.03%, which was basically consistent with the theoretical expectation of monoammonium salt (9.1%). The crystals were in anhydrous form.
[0070] The DSC graph shows two endothermic peaks, with the starting temperatures of the two endothermic peaks being 139.5°C and 206.5°C, and the peak temperatures of the two endothermic peaks being 179.83°C and 218.80°C, respectively. A large amount of endothermic heat begins to occur at 139.5°C, indicating that compared with other crystal forms, the ammonium ion in this crystal form is not easily removed and has better stability. The TGA graph shows that the weight of the crystal remains essentially unchanged below 139.5°C, and slowly decreases from 139.5°C, which is due to the endothermic heat released by ammonia. The temperature rapidly decreases from 206.5°C, which may indicate phase transition and decomposition.
[0071] Example 2: Preparation of Form E of L-glufosinate ammonium salt
[0072] L-glufosinate ammonium salt (100 g, 0.48 mol, amorphous) was added to a mixed solution of water (40 g) and methanol (300 g), heated to 68 ° C, kept warm for 10 hours, cooled to 50 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 1 hour, and then cooled to 25 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, and solid precipitated. The solution was filtered and dried to obtain Form E of L-glufosinate ammonium salt.
[0073] The XRPD analysis of the resulting crystalline form shows a spectrum as shown in Figure 4. Characteristic peaks are observed at diffraction angles 2θ = 8.884° ± 0.2°, 16.603°, 17.459° ± 0.2°, 18.101°, 18.658°, and 23.224°, with a 2θ error range of ± 0.2°, confirming the presence of this new crystalline form. Its X-ray powder diffraction data are shown in Table 2.
[0074] Table 2: XRPD patterns
[0075]
[0076] The quantitative content of the product was 97% based on a standard sample without crystal water. Ion chromatography analysis showed that the ammonium content was 8.81%, which was basically consistent with the theoretical expectation of monoammonium salt (8.82%). The crystals were in anhydrous form.
[0077] The DSC graph shows three endothermic peaks, with the onset temperatures of the three endothermic peaks being 95.5±2°C, 147±2°C, and 201±2°C, respectively; the peak temperatures of the three endothermic peaks being 113±2°C, 185.8±2°C, and 226.5±2°C, respectively. A small amount of endothermic absorption begins at approximately 95.5°C and 147°C, and a large amount of exothermic heat begins at 201°C, indicating that the ammonium ion in this crystal form is not easily removed and has good stability. The TGA graph shows that the weight of the crystal remains essentially unchanged below 95.5°C, after which it begins to slowly decrease by 1.2%, which may be due to the influence of a small amount of impurities. It begins to slowly decrease from 147°C, which is due to the endothermic absorption caused by the release of ammonia gas. It begins to decrease rapidly from 226.5°C, which may indicate decomposition.
[0078] Table 3 shows the comparison of high temperature stability data for Form D and Form E of L-glufosinate ammonium salt.
[0079] Table 3: Comparison of DSC exothermic and decomposition temperatures
[0080] No. Crystal form begins to release heat peak 1 Crystal form A in CN113480573A 110℃ 129℃ 2 Crystal form B in CN113480573A 115℃ 134℃ 3 Crystal form in CN113831364A 104℃ 115℃ 4 Crystal form D of L-glufosinate ammonium salt 139.5℃ 179.83℃ 5 Crystal form E of L-glufosinate ammonium salt 147℃ 185.833℃
[0081] Experiments show that the new crystal forms D and E of L-glufosinate ammonium salt have better high-temperature stability than the ammonium salt crystal forms in existing patents.
[0082] Example 3: Preparation of Form D of L-glufosinate ammonium salt
[0083] L-glufosinate ammonium salt (100 g, 0.48 mol, crystal form A in patent CN113480573) was added to methanol (300 g), heated to 68 ° C, kept warm for 10 hours, cooled to 35 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, solid precipitated, filtered, and dried to obtain crystal form D of L-glufosinate ammonium salt.
[0084] The obtained crystals were also subjected to XRPD testing, and the test spectrum was basically consistent with Figure 1, indicating that the obtained solid was Form D of L-glufosinate ammonium salt.
[0085] Example 4: Preparation of Form D of L-glufosinate ammonium salt
[0086] L-glufosinate ammonium salt (100 g, 0.48 mol, crystal form B in patent CN113480573) was added to methanol (300 g), heated to 68 ° C, kept warm for 12 hours, cooled to 25 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, solid precipitated, filtered, and dried to obtain crystal form D of L-glufosinate ammonium salt.
[0087] The obtained crystals were also subjected to XRPD testing, and the test spectrum was basically consistent with Figure 1, indicating that the obtained solid was Form D of L-glufosinate ammonium salt.
[0088] Example 5: Preparation of Form E of L-glufosinate ammonium salt
[0089] L-glufosinate ammonium salt (100 g, 0.48 mol, crystal form A in patent CN113480573) was added to a mixed solution of water (40 g) and methanol (300 g), heated to 68 ° C, kept warm for 10 hours, cooled to 50 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 1 hour, and then cooled to 25 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, and solid precipitated. The solution was filtered and dried to obtain crystal form E of L-glufosinate ammonium salt.
[0090] The obtained crystals were also subjected to XRPD testing, and the test spectrum was basically consistent with Figure 4, indicating that the obtained solid was Form E of L-glufosinate ammonium salt.
[0091] Example 6: Preparation of Form E of L-glufosinate ammonium salt
[0092] L-glufosinate ammonium salt (100 g, 0.48 mol, crystal form B in patent CN113480573) was added to a mixed solution of water (40 g) and methanol (300 g), heated to 68 ° C, kept warm for 10 hours, cooled to 50 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 1 hour, and then cooled to 25 ° C at a cooling rate of Tj-Tr = 1 K, kept warm for 24 hours, and solid precipitated. The solution was filtered and dried to obtain crystal form E of L-glufosinate ammonium salt.
[0093] The obtained crystals were also subjected to XRPD testing, and the test spectrum was basically consistent with Figure 4, indicating that the obtained solid was Form E of L-glufosinate ammonium salt.
[0094] Example 7: Hygroscopicity test
[0095] Experimental plan: 100 g of solid was kept at different humidity levels for 48 hours, and its mass was retested to see if there was any significant change. At the same time, its appearance was visually inspected to see if there was any significant change, so as to determine whether the crystal form was hygroscopic. The specific results are shown in Table 4.
[0096] Table 4: Changes in hygroscopicity
[0097] No. Crystal form Quality Appearance Storage temperature Humidity Quality change (%) Appearance change 1 Example 1 100.00g white powder 25℃ 65% + 0.03 No change 2 Example 2 100.00g white powder 25℃ 65% + 0.02 No change 3 Example 3 100.00g white powder 25℃ 65% + 0.03 No change 4 Example 4 100.00g white powder 25℃ 65% + 0.01 No change 5 Example 5 100.00g white powder 25℃ 65% + 0.02 No change 6 Example 6 100.00g white powder 25℃ 65% + 0.02 No change 7 Example 1 100.00g white powder 25℃ 80% + 1.12 No change
[0098] 8 Example 2 100.00g white powder 25℃ 80% + 1.23 No change 9 Example 3 100.00g white powder 25℃ 80% + 1.17 No change 10 Example 4 100.00g white powder 25℃ 80% + 1.12 No change 11 Example 5 100.00g white powder 25℃ 80% + 1.15 No change 12 Example 6 100.00g white powder 25℃ 80% + 1.18 No change
[0099] Experiments show that there is no obvious hygroscopicity when the relative humidity is low, and the hygroscopicity is also very small when the relative humidity is high.
[0100] Example 8: Stability Test
[0101] The crystals obtained in Examples 1-6 were stored at 25° C. and 60° C. for 48 hours, respectively, and their crystal form changes were retested. The specific results are shown in Table 5.
[0102] Table 5: Crystal form changes
[0103] No. Crystal form quality Temperature humidity Crystal form Appearance quality change (%) 1 Example 1 100g 25℃ 65% No change No change +0.032 Example 2 100g 25℃ 65% No change No change +0.023 Example 3 100g 25℃ 65% No change No change +0.034 Example 4 100g 25℃ 65% No change No change +0.015 Example 5 100g 25℃ 65% No change No change +0.026 Example 6 100g 25℃ 65% No change No change +0.027 Example 1 100g 60℃ 65% No change No change +0.028 Example 2 100g 60℃ 65% No change No change +0.019 Example 3 100g 60℃ 65% No change No change +0.0210 Example 4 100g 60℃ 65% No change No change +0.0111 Example 5 100g 60℃ 65% No change No change +0.0212 Example 6 100g 60℃ 65% No change No change +0.02
[0104] Experiments show that the storage stability is very good at temperatures of 25°C and 60°C.
[0105] Example 9: Dosage Formulation and Field Efficacy Experiment
[0106] The present invention is further described below in conjunction with specific formulations and field efficacy experiments. The patented crystalline technical meets the requirements of an aqueous solution and can also be developed into single- and combined-formulation formulations. The percentages below are by weight.
[0107] The following method combines preparation processing with field efficacy testing. The test agent was provided by Jiangsu Qizhou Green Chemical Co., Ltd.
[0108] Table 6: 10% refined glufosinate aqueous solution
[0109] Material Name Formula Ratio Refined Glufosinate (crystallized L-Glufosinate ammonium salt) 10% Surfactant 3% Water to make up
[0110] Field efficacy trials were conducted using the crystals of Examples 1-2 of the present invention, ammonium salt crystal forms A and B from CN113480573A, and crystal form A from CN111065270A. The aqueous solutions formulated with each crystal form were tested for physical and chemical stability, meeting production and use requirements. Field trials were also conducted on various weeds. The dosage was 120 mL / mu.
[0111] With reference to the "Guidelines for Field Efficacy Tests of Pesticides", 5 points were surveyed in each plot, each covering an area of 1 square meter. Seven days after application, the weed species, total number of plants, poisoning symptoms, number of dead plants, etc. of each treatment were recorded. Then, the plant control efficacy results were statistically analyzed, and the weed mortality rate was specifically calculated and counted.
[0112]
[0113] Table 7: Investigation results of plant protection efficacy 7 days after application
[0114]
[0115] in conclusion:
[0116] Compared with other ammonium salt crystal forms, the efficacy of ammonium salt crystal forms D and E in this patent is significantly higher by about 5%.
[0117] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.
[0118] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
Claims
1. A crystal of L-glufosinate ammonium salt, characterized in that The crystal is form D of L-glufosinate ammonium salt, and its X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 8.583°±0.2°, 17.202°±0.2°, 18.398°±0.2°, and 23.001°±0.2°.
2. The crystallization of L-glufosinate ammonium salt according to claim 1, characterized in that The X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 17.738°±0.2°, 21.977°±0.2°, 22.721°±0.2°, and 25.716°±0.2°.
3. The crystallization of L-glufosinate ammonium salt according to claim 2, characterized in that The X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 32.980°±0.2°, 35.920°±0.2°, and 39.509°±0.2°.
4. The crystallization of L-glufosinate ammonium salt according to claim 1, characterized in that The X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt has characteristic peaks at 2θ angles of 8.583°±0.2°, 17.202°±0.2°, 17.738°±0.2°, 18.398°±0.2°, 21.977°±0.2°, 22.721°±0.2°, 23.001°±0.2°, 25.716°±0.2°, 32.980°±0.2°, 35.920°±0.2°, and 39.509°±0.2°.
5. The crystal of L-glufosinate ammonium salt according to claim 1, characterized in that The X-ray powder diffraction pattern of the crystalline form D of the L-glufosinate ammonium salt is shown in FIG1 .
6. The crystal of L-glufosinate ammonium salt according to claim 1, characterized in that The spectrum of the crystalline form D of the L-glufosinate ammonium salt measured by differential scanning calorimetry shows two endothermic peaks, and the starting temperatures of the two endothermic peaks are 139.5±2°C and 206.5±2°C, respectively. The spectrum of the crystalline form D of the L-glufosinate ammonium salt measured by thermogravimetric analysis shows that it loses 4.3±0.2% of its weight when heated from 139.5±2°C to 206.5±2°C.
7. The crystal of L-glufosinate ammonium salt according to claim 1, characterized in that The spectrum of the crystalline form D of the L-glufosinate ammonium salt measured by differential scanning calorimetry is shown in FIG2 , and the combined spectrum of the spectrum measured by differential scanning calorimetry and thermogravimetric analysis is shown in FIG3 .
8. The crystal of L-glufosinate ammonium salt according to claim 1, characterized in that The crystalline form D of the L-glufosinate ammonium salt is an anhydrous crystalline form.
9. A crystal of L-glufosinate ammonium salt, characterized in that: The crystal is form E of L-glufosinate ammonium salt, and its X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 8.884°±0.2°, 16.603°±0.2°, 17.459°±0.2°, 18.101°±0.2°, 18.658°±0.2°, and 23.224°±0.2°.
10. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt also has characteristic peaks at one or more of the 2θ angles of 19.513°±0.2° and 33.221°±0.2°.
11. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt has characteristic peaks at 8.884°±0.2°, 16.603°±0.2°, 17.459°±0.2°, 18.101°±0.2°, 18.658°±0.2°, 19.513°±0.2°, 23.224°±0.2°, and 33.221°±0.2°.
12. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The X-ray powder diffraction pattern of the crystalline form E of the L-glufosinate ammonium salt is shown in FIG4 .
13. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The spectrum of the crystalline form E of the L-glufosinate ammonium salt measured by differential scanning calorimetry shows three endothermic peaks, and the onset temperatures of the three endothermic peaks are 95.5±2°C, 147±2°C and 201±2°C, respectively; the spectrum of the crystalline form E of the L-glufosinate ammonium salt measured by thermogravimetric analysis shows that when heated from 95.5±2°C to 147±2°C, it loses 1.2±0.2% of its weight, and when heated from 147±2°C to 201±2°C, it loses 2.89±0.2% of its weight.
14. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The spectrum of the crystal form E of the L-glufosinate ammonium salt measured by differential scanning calorimetry and the combined spectrum measured by thermogravimetric analysis are shown in FIG5 .
15. The crystal of L-glufosinate ammonium salt according to claim 9, characterized in that The crystalline form E of the L-glufosinate ammonium salt is an anhydrous crystalline form.
16. A method for preparing the crystal of L-glufosinate ammonium salt according to any one of claims 1 to 8, characterized in that: The preparation method of the crystal comprises: adding L-glufosinate ammonium salt to an organic solvent, heating to 65-90° C. for a first heat preservation, then cooling at a cooling rate with a difference of 1-5K between the external temperature and the internal temperature to -10-35° C., performing a second heat preservation, precipitating a solid, filtering the solid, and drying the obtained solid to obtain the crystal form D of L-glufosinate ammonium salt.
17. A method for preparing the crystal of L-glufosinate ammonium salt according to any one of claims 9 to 15, characterized in that: The crystal preparation method comprises: adding L-glufosinate ammonium salt to a mixed solvent of an organic solvent and water, heating to 65-90°C for a first heat preservation, then cooling to 40-60°C at a cooling rate with a difference of 1-5K between the external temperature and the internal temperature, then cooling to -10-35°C at a cooling rate with a difference of 1-5K between the external temperature and the internal temperature, then heating for a third time, precipitating a solid, filtering the solid, and drying the obtained solid to obtain the crystal form E of L-glufosinate ammonium salt.
18. The method for preparing the crystal of L-glufosinate ammonium salt according to claim 16 or 17, characterized in that: In the process of preparing the crystalline forms D and E of L-glufosinate ammonium salt, the organic solvent is a combination of one or more selected from alcohol solvents, ketone solvents and nitrile solvents.
19. The method for preparing the crystal of L-glufosinate ammonium salt according to claim 16 or 17, characterized in that: In the process of preparing the crystal forms D and E of L-glufosinate ammonium salt, the mass ratio of the L-glufosinate ammonium salt to the organic solvent is 1:1-20.
20. The method for preparing the crystal of L-glufosinate ammonium salt according to claim 17, characterized in that: In the process of preparing the crystalline form E of L-glufosinate ammonium salt, the mass ratio of the water to the organic solvent is 0.05-0.3:
1.
21. A herbicide composition comprising an active ingredient and a carrier, characterized in that: The active ingredient comprises at least one of the crystalline form D of the L-glufosinate ammonium salt according to any one of claims 1 to 8 and the crystalline form E of the L-glufosinate ammonium salt according to any one of claims 9 to 15.